Pengaruh Customer Value Dan Shariah Compliance Terhadap Loyalitas Melalui Kepuasan Sebagai Variabel Intervening (Studi Kasus Pada Nasabah PT. Bank Sumut Unit Usaha Syariah) - Sari, Novita; Lestari Nasution, Annio Indah; Armayani Hasibuan, Reni Ria (Universitas Labuhanbatu, 2024)
The purpose of the study was to determine the effect of customer value and shariah compliance on customer loyalty through satisfaction as an intervening variable on customers at Bank Sumut Syariah KCP Karya Medan. Research II quantitative wear. Bank customers become polluting in the study. This study used the technique of accidental sampling. The sample size was 40 respondents.Using primary data that is the spread of questionnaires directly. Using data analysis data quality test, classical assumption test, hypothesis test, F test (simultaneous) and path analysis test using SPSS version 23.0. The results of this study indicate that (i) customer value has a positive and significant effect on customer loyalty (ii) shariah compliance has a positive and significant effect on customer loyalty (iii) satisfaction has a positive and significant effect on customer loyalty (iv) customer value does not affect loyalty through customer satisfaction as an intervening variable (v) shariah compliance does not affect loyalty through customer satisfaction customer loyalty.